PENGENALAN MANAJEMEN BISNIS SYARIAH DALAM INDUSTRI KERAJINAN TANGAN DESA CIBITUNG WETAN, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR - Rully Trihantana; Ermi Suryani; Citra Praditya Rahayu (Jurnal Pengabdian Kepada Masyarakat Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2022)
Sharia Business Management is still not widely known by the public, especially people who are relatively far from the hustle and bustle of big cities in Indonesia. One of them is the community of Cibitung Wetan Village, Pamijahan District, Bogor Regency. Society generally knows about Islam as a way of life in relation to Allah Subhanahu Wa Ta'ala, humans and the environment. The general public is also familiar with the existence of Islamic economics which includes zakat, infaq, shodaqoh and waqf. However, regarding matters that are more specific to Islamic economics, namely sharia business management, people generally do not know about sharia business management. At the same time, some people have handicraft home industries. This is an opportunity in community service activities that actually sharia business management will direct the management of the handicraft home industry to be even better, because it is in line with the beliefs of the people who have so far made Islam a way of life, and of course it is in line with the hope of becoming more prosperous.